Features of the application of multimedia technology in the preparation (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2016)
In the article the features of application of multimedia technology in the process of preparation. Education usingcomputer as a means of gaining, mastering, solidifying knowledge, the development of thinking and control of these processes bringstogether a variety of technologies: from simple programs to reinforce skills to intelligent tutoring systems that provide reflexive trainingmanagement, conduct dialogue with student, language, close to natural, and upon the accumulation of experience, improve the strategyof solving educational assignments.All the above mentioned proves the need of multimedia in the process of technological education. A modern education institutionhas to form in students mind not only a certain set of competencies but also a desire for self-education, realization of their abilities. Anecessary condition for the development of these processes is to promote teaching and learning activities. The multimedia plays animportant role in solving this problem, creating the significant opportunities to enhance educational activities. Widespread use ofmultimedia in the process of preparation makes it possible to implement the principle of «learning with enthusiasm» and then technicaldisciplines will have an equal chance to be favorite for students.